Epidemiologic consequences of preclinical transmission of foot-and-mouth disease virus in cattle - Scharzenberger, Stormy; Humphreys, John M.; Rigney, Columb; Freifeld, Alexis; Stenfeldt, Carolina; Arzt, Jonathan (Frontiers in Veterinary Science, 2025)
Foot-and-mouth disease virus (FMDV) can be transmitted during the incubation phase, before clinical detection, but the epidemiological consequences of this preclinical infectious period have not been fully assessed in cattle. Using experimental data derived from transmission studies performed in vivo, we parameterized a state-transition model and simulated FMDV outbreaks across three U.S. regions under varying durations of preclinical infectiousness. We evaluated multiple epidemiologic outcomes under both optimal (1 day after clinical onset) and suboptimal (4 days after clinical onset) detection scenarios. The modeled output demonstrated that even a single day of preclinical transmission significantly increased outbreak magnitude, spatial extent, and duration. These effects were magnified under suboptimal detection and when simulating low-virulence virus strains with prolonged preclinical phases. Optimal response consistently reduced outbreak severity, with greater mitigation observed in the Eastern and Central U.S. as the preclinical phase lengthened. Our findings demonstrate that omission of preclinical transmission from FMD models results in systematic underestimation of outbreak impacts. Incorporating incubation phase transmission is essential for realistic epidemic forecasting, effective preparedness planning, and region-specific response prioritization.